THE IMPACT OF YOGIC PRACTICES ON TEST-ANXIETY OF HEARING AND HEARING IMPAIRED HIGH SCHOOL STUDENTS - Dr. M.Nirmala Rekha (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Now days, every student, whether disabled or normal, wants to do exceed in each and every sphere of life and also wants to touch the heights of success at global world. The changing situation of society at global level has forced the individuals, especially the disabled ones, to concentrate on their efforts on different dimensions of life. It is a matter of great concern that the abilities and potentials of disabled adolescents have not yet been fully explored and tackled, but practically it is a great loss of human resources, which, if discovered, matured, appropriately channelized and utilized could add a new force to the progression of the society. Children with disabilities are particularly prone to various physical, social, mental and emotional problems which are directly related to some limitations preventing them from enjoying normal life